Comparative electrochemical study for the polymorphic MnOx/rGO composites derived from well-stacked MnO2/GO templates as for Li-rechargeable battery electrodes. (10th November 2018) - Ju, Ji Young; Ji, Seulgi; Kim, Jin Kyu; Choi, Seul Ki; Unithrattil, Sanjith; Lee, Sun Sook; Kang, Yongku; Kim, Yongseon; Im, Won Bin; Choi, Sungho
Abstract: The microstructure and electrochemical behavior of MnOx @reduced graphene oxide (rGO) composites derived from a MnO2 /GO template are thoroughly investigated. An as-prepared MnO2 /GO mixture is gradually converted to MnO2 /rGO in a reduction process and is subsequently annealed under specific conditions to form the Mn3 O4 /rGO composites. The overall Li + conversion reactions are visualized and the stability of the transformed MnO x phases is evaluated using density function theory calculations. The semispherical Mn3 O4 anchored composite exhibits stable electrode performances, including both the Li + anode and the Li + -air cathode catalyst, induced by the electrochemically favorable composite with an effective large contact area between the active materials and the electronic conductive rGO. This provides a comparative way of designing the electrode for multiphase metal oxide-based composite electrodes considering the specific electrochemical reactions in view of materials engineering. Graphical abstract: Highlights: Comparative evaluating the electrochemical behaviors for MnO2 / and Mn3 O4 /rGO. Providing the cycle performance for polymorphic MnOx /rGO composites electrode. GO reduction with well-stacked frame is crucial for MnOx /GO composite electrodes.